RECOGNIZING DEVELOPMENTAL DELAY OF CHILDREN UNDER 42 MONTHS IN AZERBAIJAN - Ulviyya Mirzayeva, (International Journal of Innovative Technologies in Social Science, 2025)
According to the U.S. Centers for Disease Control and Prevention (CDC), 15% of children under the age of 17 experience one or more developmental disorders. In the context of Azerbaijan, the limited knowledge among parents regarding the stages of child development and the signs of developmental delays suggests that these numbers may be even higher. Parents typically observe developmental delays at later ages and often turn to local polyclinics or physicians, which prolongs the process. Delayed detection and the need for specialist referrals are among the main reasons for prolonging process. The purpose of this study, which we carried out in order to obtain more objective information about this issue, is to investigate the risk of developmental delay in children who are considered to show typical development between 1-42 months, and whose developmental delay is not noticed by parents and others, and in which areas of development this delay is more common. The research used the adapted version of the Guide to Monitoring Child Development (GMCD) tool   to track and assess a child's growth, milestones, and developmental progress to ensure they are meeting age-appropriate standards and to identify any potential issues early on. Early intervention specialists from 11 regions of Azerbaijan determined developmental difficulties of 138 children aged birth to 42 months. The fact that this tool is currently a recognized and accepted test by the Ministry of Health of Azerbaijan and at the same time many specialists from different regions have been trained to perform this test, as well as the fact that the test itself is simple to use has played an important role in the selection of this screening tool.